Soil fertility status of some of the intensive crop growing areas under major agroecological zones of Bangladesh (Bangladesh Journal of Agricultural Research, 2016)
Laboratory studies on soil fertility evaluation was carried out across major agroecological zones (AEZs) of Bangladesh to know the nutrient status of soils and to relate those with soil properties like pH, organic matter, CEC, and clay content. Thirty five composite soil samples were collected from intensive crop growing sites, which covered 17 AEZs of Bangladesh. After proper processing, the samples were analyzed for texture, pH, organic carbon, CEC, exchangeable cations (K, Ca, Mg and Na), total N, available P and S following standard methods. The textural class of the soils collected from AEZ 12 and 13 appeared to be mostly clay. Clay loam soil was found in AEZ 4, 8, 9, 11, 25 and 28. Loamy soil was seen in AEZ 1 while AEZ 22, 23 and 29 were mostly sandy textured. The results revealed that 65.7% of the tested soil was acidic while 25.7% was alkaline in nature. All the tested soils showed lower pHKCl compared to pHH2O thus possessed negative charge. About 68.6% of the collected soils contained low (1.10-1.70%) level of organic matter, 25.7% soils retained it at medium level (1.71-2.40) and 5.7% soils at very low level (